2016
DOI: 10.1590/s0100-204x2016000600005
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α or estradiol benzoate to induce ovulation in timed artificially inseminated dairy cows

Abstract: -The objective of this work was to compare two types of ovulation inducers -estradiol benzoate (EB group) or prostaglandin F2α (PG group) -, in postpartum dairy cows subjected to timed artificial insemination (TAI). Lactating Holstein-Gir crossbred cows (n=118) with 60 to 120 days of milk production were used in this study. All cows were treated with an intravaginal progesterone-releasing device (CIDR) plus 2 mg of estradiol benzoate (EB) on day 0. The CIDR inserts were removed on day 9, and all cows received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
12
0
3
Order By: Relevance
“…Our recent data, in which spayed cows were treated with 300 mg of PGF analogue (D-cloprostenol), 10.5 mg of GnRH analogue (Buserelin Acetate) or saline (0.9% of NaCl), demonstrated that only cows treated with GnRH had increasing of plasma LH concentration after treatment (not published data). Moreover, when PGF were used as ovulatory stimulus in dairy cows, it was observed an association between follicle vascularization and the time to ovulation [6]. This data led us to further hypothesize that PGF, acting mainly by a local mechanism, requires a higher developmental status of pre-ovulatory follicles compared to the systemic-mediated action of ECP.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our recent data, in which spayed cows were treated with 300 mg of PGF analogue (D-cloprostenol), 10.5 mg of GnRH analogue (Buserelin Acetate) or saline (0.9% of NaCl), demonstrated that only cows treated with GnRH had increasing of plasma LH concentration after treatment (not published data). Moreover, when PGF were used as ovulatory stimulus in dairy cows, it was observed an association between follicle vascularization and the time to ovulation [6]. This data led us to further hypothesize that PGF, acting mainly by a local mechanism, requires a higher developmental status of pre-ovulatory follicles compared to the systemic-mediated action of ECP.…”
Section: Discussionmentioning
confidence: 88%
“…These studies support the hypothesis that the PGF can induce ovulation of dominant follicle (DF) by an independent mechanism of luteolysis. More recently, im injection of PGF has been successfully used as an ovulation inducer in TAI protocols for beef [5] and dairy cows [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent experiment, in which ovariectomized cows were treated with a PGF analogue (d-cloprostenol), a GnRH analogue (buserelin acetate), or saline, demonstrated that only cows treated with GnRH had increased plasma LH concentration after treatment (unpublished data). Moreover, when PGF was used as an ovulatory stimulus in dairy cows, an association between follicle vascularization and the interval to ovulation was observed (Pfeifer et al, 2016). These results led us to further hypothesize that PGF, acting mainly via a local mechanism, requires a higher developmental status of pre-ovulatory follicles compared to the systemic-mediated action of ECP.…”
Section: Discussionmentioning
confidence: 86%
“…Although the number of animals included in the present study is low, these evidences lead us to infer that PGF has no ovulatory effect in buffaloes. Previous studies have indicated that d-cloprostenol has an ovulatory effect similar to that of EB in TAI protocols, resulting in similar ovulation and pregnancy rates in dairy (Pfeifer et al, 2016;Castro et al, 2018) and beef cows (Pfeifer et al, 2014(Pfeifer et al, , 2018. Moreover, the injection of PGF has also been reported to act as an ovulatory stimulus in prepubertal heifers (Pfeifer et al, 2009;Leonardi et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Prostaglandin F 2α (PGF) analogs are commonly used to induce luteolysis in estrous synchronization programs in cattle (Pursley et al, 1995;Weems et al, 2006;Colazo & Mapletoft, 2014). However, PGF is also able to hasten and synchronize ovulation in cattle (Pfeifer et al, 2014;Pfeifer et al, 2016;Castro et al, 2017) independent of its luteolytic action (Leonardi et al, 2012). Previously, we observed that d-Cloprostenol (PGF analog) had a similar ovulatory effect to that of estradiol benzoate in timed artificial insemination (TAI) protocols, resulting in similar ovulation and pregnancy rates in dairy (Pfeifer et al, 2016;Castro et al, 2017) and beef cows (Pfeifer et al, 2014;Pfeifer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%